2012 IEEE International Symposium on Sustainable Systems and Technology (ISSST) 2012
DOI: 10.1109/issst.2012.6228020
|View full text |Cite
|
Sign up to set email alerts
|

Cultured meat: The systemic implications of an emerging technology

Abstract: Cultured meat -edible muscle tissue grown in a laboratory or factory (carnery) without the need of a whole animal -was shown to be feasible in 2000 [1] and several researchers have since suggested that large-scale production is possible [2][3][4][5]. Using ESEM principles as a guide, this investigation represents a preliminary attempt to shed light on some of the environmental, economic, and social implications of this emerging technology. The ultimate goal is to facilitate adaptive management of its commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…While cultured meat may provide an answer or partly solution to these issues, it remains to be investigated whether consumers will also perceive cultured meat and its way of production as a solution that is realistic, feasible and effective. Mattick and Allenby (2012) highlighted the possible positive and negative economic, social and environmental implications of a shift to what they call "factory-grown meat". They pointed to a considerable amount of uncertainty with respect to regulatory issues, technology adoption and production processes.…”
Section: Preliminary Insights From Consumer Studiesmentioning
confidence: 99%
“…While cultured meat may provide an answer or partly solution to these issues, it remains to be investigated whether consumers will also perceive cultured meat and its way of production as a solution that is realistic, feasible and effective. Mattick and Allenby (2012) highlighted the possible positive and negative economic, social and environmental implications of a shift to what they call "factory-grown meat". They pointed to a considerable amount of uncertainty with respect to regulatory issues, technology adoption and production processes.…”
Section: Preliminary Insights From Consumer Studiesmentioning
confidence: 99%
“…While these taste concerns were expressed prior to the IVM hamburger event, the responses of the hamburger taste testers indicate that this remains an area where further work is needed. Other potential concerns articulated by researchers include IVM costing more to produce than conventional meat (1,27) , causing significant changes to agricultural economies if it becomes commercially viable (28,29) and leading to increased industry consolidation and corporate power in the food system (18,21) . Marcu et al (10) also found that some individuals rejected IVM entirely as they felt that it was an unnecessary development.…”
Section: Public Exposure To In Vitro Meatmentioning
confidence: 99%
“…However practically, genetic mutations over the time are likely to limit the production potential of an embryonic stem cell. Also, these cells would have to be stimulated to differentiate into myoblasts (Mattick and Allenby 2010;Datar and Betti 2010). Further, such stimulation of embryonic stem cells does not promise the retention of the same proliferative characteristics.…”
Section: A) Embryonic Stem Cellsmentioning
confidence: 99%